Prospective study on cervical neoplasia: presence of HPV DNA in cytological smears precedes the development of cervical neoplastic lesions - Tachezy, R; Saláková, M; Hamsíková, E; Kanka, J; Havránková, A; Vonka, V (Sexually transmitted infections, 2003)
OBJECTIVES: The principal aim of the study was to verify whether HPV infection in healthy women, as determined by HPV DNA detection, was associated with an increased risk of development of cervical lesions. METHODS: Cervical smears collected at enrolment into the prospective study conducted in Prague during 1975-83 were tested for the presence of HPV DNA by means of a polymerase chain reaction (PCR) using the general GP5/6 primers and a mixture of primers specific for the E6 gene. 120 smears from patients in whom cervical neoplasia had been detected in the course of the prospective study and 208 smears from control women who had remained healthy throughout the observation period were analysed. Patients and controls were matched by age, number of sexual partners, age at first intercourse, and smoking habit. Patients were divided into three groups, A, B, and C, according to their cytological, colposcopic, and histological findings at enrolment. Group A consisted of 67 women found ill at enrolment, group B of 26 women with slightly suspicious findings, while group C comprised 27 women with normal findings at enrolment. In addition, sera taken at enrolment from these patients and controls were tested for the presence of antibodies reactive with virus-like particles (VLPs) of HPV 16, 18, and 33. RESULTS: For the whole cohort, there was a statistically highly significant difference in the presence of HPV DNA between patients and controls. Furthermore, the difference in the presence of HPV DNA between patients and controls was highly significant not only in those who had been found ill at enrolment (group A) but, most importantly, also in women who had developed the disease in the course of the follow up (groups B and C). Women positive for HPV DNA possessed HPV antibodies to VLP16, 18 and 33 significantly more often than those who were free of HPV DNA. CONCLUSION: This indicated that healthy women who were positive for HPV DNA at enrolment were at an increased risk of developing cervical neoplasia (OR = 18.5; CI 5.9 to 57.6).
Keywords: nádory děložního čípku; Polymerase Chain Reaction; polymerázová řetězová reakce; lidé středního věku; Papillomavirus Infections; vaginální stěr; Uterine Cervical Dysplasia; Uterine Cervical Neoplasms; Humans; Middle Aged; Papillomaviridae; Female; epidemiologické metody; Epidemiologic Methods; ženské pohlaví; dysplazie děložního hrdla; Cervix Uteri; DNA virů; Adult; cervix uteri; dospělí; lidé; infekce papilomavirem; DNA, Viral; Vaginal Smears